2020
DOI: 10.1177/1098612x19895940
|View full text |Cite
|
Sign up to set email alerts
|

2020 AAFP Feline Retrovirus Testing and Management Guidelines

Abstract: Clinical importance: Feline leukemia virus (FeLV) and feline immunodeficiency virus (FIV) infections are found in cats worldwide. Both infections are associated with a variety of clinical signs and can impact quality of life and longevity. Scope: This document is an update of the 2008 American Association of Feline Practitioners' feline retrovirus management guidelines and represents current knowledge on pathogenesis, diagnosis, prevention and treatment of retrovirus infections in cats. Testing and interpretat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
207
0
40

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(278 citation statements)
references
References 132 publications
2
207
0
40
Order By: Relevance
“…Changes in the total leukocyte count are related to the reduction in the number of circulating neutrophils, mainly in the acute phase of infections and later in the immunosuppression phase, due to insufficient myelopoiesis (Shelton et al, 1990;Costa et al, 2017;Turinelli & Gavazza, 2018). Lymphopenia is related to the onset of immunosuppression, with a decrease in the number of CD4 and CD8 cells (Hofmann-Lehmann et al, 1997;Novo et al, 2016;Little et al, 2020 Regarding biochemical changes, we observed a tendency towards hyperproteinemia in FIV positive cats. Hartmann (2011) and Liem et al (2013) reported an increase in plasma globulins in cats as a result of the polyclonal expansion of B lymphocytes in response to FIV.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Changes in the total leukocyte count are related to the reduction in the number of circulating neutrophils, mainly in the acute phase of infections and later in the immunosuppression phase, due to insufficient myelopoiesis (Shelton et al, 1990;Costa et al, 2017;Turinelli & Gavazza, 2018). Lymphopenia is related to the onset of immunosuppression, with a decrease in the number of CD4 and CD8 cells (Hofmann-Lehmann et al, 1997;Novo et al, 2016;Little et al, 2020 Regarding biochemical changes, we observed a tendency towards hyperproteinemia in FIV positive cats. Hartmann (2011) and Liem et al (2013) reported an increase in plasma globulins in cats as a result of the polyclonal expansion of B lymphocytes in response to FIV.…”
Section: Discussionmentioning
confidence: 79%
“…The feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV) are two retroviruses that promote a progressive imbalance in the metabolism and immune system of the affected animals (Hosie et al, 2009;Hartmann, 2011;Teixeira et al 2019). Diagnosis of FIV/FeLV infections is performed by associating the clinical signs presented by the cats to complementary laboratory tests (Teixeira et al, 2007;Little et al, 2020). Diagnosis is necessary for the practice of preventive measures such as early vaccination and the initiation of necessary care in the case of positive animals (Levy et al, 2008;Westman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Feline leukemia and feline immunodeficiency viruses (FeLV and FIV, respectively) are retroviruses that affect domestic cats. Feline leukemia is a severe disease with several outcomes associated mainly with the immune response of the cat [1][2][3]. Disease outcomes range from "abortive infection" (a strong immune response eliminates the virus at the initial stages of the infection) to "regressive infection" (the virus remains integrated in the haemopoietic stem cells in the bone marrow) and "progressive infection" (when the virus is constantly expressed, associated to persistent viremia and progression of the FeLV infection to related diseases) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Every effort should be made to ensure that cats are healthy before vaccination. However, concurrent illness (including retroviral infections) does not necessarily preclude vaccination 34. The 2020 AAFP Feline Retrovirus Testing and Management Guidelines state that vaccines should not be avoided in cats with retroviral infection because they can develop more severe clinical disease related to FPV and upper respiratory tract infections after natural exposure compared with un infected cats 34.…”
mentioning
confidence: 99%